Optimizing Arbitration for Business Dispute Settlement among Business Actors in Bengkulu: An Empirical Socio-Legal Study - Novran Harisa (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study aims to analyze the optimization of arbitration as a mechanism for business dispute settlement in Bengkulu from an empirical socio-legal perspective. Although arbitration is formally recognized under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, its practical use among local business actors remains limited. This research applies a socio-legal method combining legal-normative analysis and empirical field inquiry. The normative component examines the Indonesian legal framework on arbitration, including Law Number 30 of 1999, relevant Supreme Court regulations, arbitration principles, and alternative dispute resolution literature. The empirical component investigates how business actors in Bengkulu perceive and use arbitration in practice. Data were collected from 23 purposively selected informants, consisting of local business actors, MSME representatives, cooperative actors, legal practitioners, academics, and institutional stakeholders. Data collection techniques included semi-structured interviews, document analysis, and normative legal review. The data were analyzed using qualitative thematic analysis combined with legal-normative interpretation. This design allows the study to distinguish between the formal legal framework governing arbitration and the practical perceptions, barriers, and dispute resolution behavior of business actors in Bengkulu. The findings show that arbitration has not yet become a dominant mechanism for resolving business disputes in Bengkulu. Its limited use is influenced by weak legal literacy, poor understanding of arbitration clauses, limited institutional access, perceived high cost, and a strong preference for informal or kinship-based settlement. Local business actors tend to prioritize negotiation and compromise because these methods are considered familiar, less confrontational, and compatible with local business culture. The study concludes that arbitration should be developed not as a replacement for local negotiation practices, but as part of a hybrid dispute resolution model supported by legal literacy, simplified arbitration clauses, transparent costs and procedures, institutional support, and consistent court enforcement.